(untitled) (Docentes 2.0 Journal, 2022)
Computer Legislation refers to the use of computer media; one of its main objectives is to protect and establish limitations and rules so that computing does not become a means by which the purposes for which it was created are diverted. This research aims to design a didactic model based on active learning through didactic strategies, supported by a technological platform to promote the teaching of laws and their articles related to computer crimes. The present investigation is framed under the deductive method, positivist paradigm, with a quantitative approach, of experimental design and descriptive type; however, the research will be carried out in the Faculty of Informatics of the Autonomous University of Querétaro, in which it will be handled with the use of a technological platform in which students can interact and thus obtain more excellent knowledge about the laws. The study seeks that students, with an active learning model as a tool, can have a perfect understanding of a specific subject. In addition, to know the importance of computer crimes and laws.